Nutrient-dependent allometric plasticity in a male-diphenic mite - Rhebergen, Flor T.; Stewart, Kathryn A.; Smallegange, Isabel M. (bioRxiv, 2021)
Male secondary sexual traits often scale allometrically with body size. These allometries can be variable within species, and may shift depending on environmental conditions such as food quality. Such allometric plasticity has been hypothesized to initiate local adaptation and evolutionary diversification of scaling relationships, but is under-recorded, and its eco- evolutionary effects are not well understood. Here, we test for allometric plasticity in the bulb mite (Rhizoglyphus robini) in which large males tend to develop as armed adult fighters with thickened third legs, while small males become adult scramblers without thickened legs. We first examined the ontogenetic timing for size- and growth-dependent male morph determination, using experimentally amplified fluctuations in growth rate throughout juvenile development. Having established that somatic growth and body size determine male morph expression immediately before metamorphosis, we examined whether the relationship between adult male morph and size at metamorphosis shifts with food quality. We found that the threshold body size for male morph expression shifts towards lower values with deteriorating food quality, confirming food-dependent allometric plasticity. Such allometric plasticity may allow populations to track prevailing nutritional conditions, potentially facilitating rapid evolution of allometric scaling relationships.